SAT0027 Immunomodulatory effects of MGD010, a dart® molecule targeting human B-CELL CD32B and CD79B. (15th June 2017) - Chen, W; Shankar, S; Lohr, J; Yao, X-T; Li, H; Chen, X; Muth, J; Gal-Edd, N; Bonvini, E; Johnson, S; Pandya, N; Moore, PA; et al.
Abstract : Background: B-cell targeted therapeutics have proven efficacious in the treatment of autoimmune diseases, generating impetus to develop alternate strategies that provide activity with rapid onset and no B-cell depletion. To this end, MGD010, a bispecifc DART® molecule, was designed to exploit the inhibitory function of the checkpoint molecule, CD32B, (FcγRIIb) via its simultaneous co-ligation with the BCR component, CD79B. Initial phase 1 studies performed in healthy subjects demonstrated MGD010 was well tolerated in a single-dose, dose escalation to up to 10 mg/kg, with no evidence of peripheral B-cell activation or depletion. MGD010 exhibited pharmacokinetic properties of an antibody-based molecule, with dose-dependent B-cell occupancy saturating at >1mg/kg and diminished propensity for ex-vivo BCR-induced B-cell activation (1). To further understand the potential for MGD010 to modulate ongoing immune responses, the impact of MGD010 on the immune response to Hepatitis A (HAV) vaccination, a T-cell dependent neo-antigen challenge, was evaluated in normal healthy subjects. Objectives: To determine effects of MGD010 on humoral and cellular immune responses in normal healthy volunteers. Methods: This was an open label, placebo controlled cohort-expansion in normal healthy volunteers. Subjects (n=8 per group) were randomly assigned to receive an IV administration of a single dose of 3 or 10 mg/kg MGD010 or placebo. All subjects received a single intramuscular dose of hepatitis A vaccine (HAV) (1.0 mL or ∼50U) 24 hours after administration of MGD010 or placebo. Subjects were monitored for adverse events for 56 days after administration of drug or placebo. Analyses included peripheral lymphocyte counts and immunophenotyping, determination of serum immunoglobulin levels, seroconversion rate of HAV and quantification of serum HAV IgG concentration. Results: Twenty-four (24) healthy subjects were enrolled for the study and 23 completed the study. One subject discontinued prior to completion due to inability to follow study procedures. There were no severe adverse events in subjects who received 3 or 10 mg/kg MGD010. The only serious adverse event reported in t in a subject who had received placebo and was not drug related. There were no CTCAE grade 3 or higher adverse events related to MGD010. Consistent with prior observations (1), ex vivo flow cytometric analysis confirmed dose-dependent MGD010 binding to peripheral B cells without B-cell depletion, accompanied with decreased surface BCR and CD40 expression as well as a moderate decrease in total serum IgM levels. Reduced HAV seroconversion rates were observed in subjects treated with MGD010 as compared to placebo, with significantly lower HAV-specific IgG levels in subjects treated with MGD010 compared with placebo group ( P <0.05). Conclusions: These studies demonstrate that by pharmacologically exploiting the activity of the checkpoint molecule CD32B in combination with the BCR CD79B component, a single dose administration of either 3 or 10 mg/kg MGD010 delivers an immunomodulatory effect that effectively counters B-cell function. Together with a good safety profile, these data provide compelling rationale for further developing MGD010 as a therapeutic modality for autoimmune diseases. References: Pandya, N et al., EULAR16–4079. Acknowledgements: . Disclosure of Interest: W. Chen Employee of: MacroGenics, S. Shankar Employee of: MacroGenics, J. Lohr Employee of: MacroGenics, X.-T. Yao Employee of: MacroGenics, H. Li Employee of: MacroGenics, X. Chen Employee of: MacroGenics, J. Muth Employee of: MacroGenics, N. Gal-Edd Employee of: MacroGenics, E. Bonvini Shareholder of: MacroGenics, Employee of: MacroGenics, S. Johnson Shareholder of: MacroGenics, Employee of: MacroGenics, N. Pandya Shareholder of: MacroGenics, Employee of: MacroGenics, P. Moore Shareholder of: MacroGenics, Employee of: MacroGenics, J. Wigginton Shareholder of: MacroGenics, Employee of: MacroGenics